THE INFLUENCE OF COUNTRY OF ORIGIN AND EWOM ON PURCHASE INTENTION WITH THE VARIABLE MEDIA BRAND IMAGE OF COMPUTER PRODUCTS IN JAKARTA - Andree Gunawan; Rodhiah Rodhiah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The purpose of this study was to test the Influence of Country of origin, and Electronic Word of Mouth (eWOM) on Purchase Intention with Product Brand Image Mediation Variable komputer "X" in Jakarta. In this study, the population in this study was consumers who used the product komputer "X". The number of samples collected was 214 respondents, the research design was descriptive with a cross-sectional approach. This study used a non-probability sampling collection method with purposive sampling techniques through Google Forms. SEM analysis technique using smart partial least square (PLS) software. The results showed that Country of origin, and Electronic Word of Mouth (eWOM) can positively influence purchase intention, "X" computer products in Jakarta. Brand Image can positively influence the purchase intention of computer product "X" in Jakarta and Country of origin, and Electronic Word of Mouth (eWOM) can positively influence the purchase intention of computer product "X" in Jakarta through Brand Image. Brand "X" needs to pay attention to the Country of origin, Electronic Word of Mouth (eWOM) and Brand Image in increasing the purchase Intention / Intention to buy consumers. Keywords: Country of Origin, Electronic Word of Mouth (eWOM), Purchase Intention, Brand Image